Study on properties of sugarcane bagasse fiber filled Polypropylene composites - Nur Sheli Akma Ramli (Universiti Malaysia Perlis, 2008)
Bagasse fiber is a residue of a sugarcane milling process. In this research, bagasse fiber has been used as filler in polypropylene (PP) resin to open up further possibilities in waste management. The chemical treatment using polypropylene-graft maleic anhydride (MAPP) was carried out to modify the fiber properties.The effect of fiber treatment and the fiber content on the composite properties were studied. The compounding process was used as the PP/bagasse fiber composites fabrication. The properties of PP/bagasse fiber composites were investigated through mechanical and physical testing. The presence of MAPP as fiber treatment has accommodated better mechanical and physical properties for PP/bagasse fiber composites. This has been proved by morphology studied which compatibilized PP/bagasse composite has smooth surface without fiber pulled out. From tensile test, tensile strength and elongation at break increased with increasing filler content while modulus of elasticity decreased for both compatibilized and uncompatibilized PP/bagasse fiber composite. The addition of bagasse fiber in PP has decreased the flexural strength and flexural modulus for both compatibilized and uncompatibilized PP/bagasse fiber composites. Based on water absorption behaviour, it can be observed that the compatibilized PP/bagasse fiber composites showed lower water absorption behaviour compared to the uncompatibilized one.